Pelajaran Hidup dari The Doctor Valentino Rossi : Spirit Impresi Pendidikan Islam yang Menghidupkan - Robingun Suyud El Syam; Sunaryo Sunaryo; Hermawan Hermawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to examine the life lessons of The Doctor Valentino Rossi, in order to create a spirit of life-giving impressions of Islamic education, by analyzing them to provide a better understanding of the theme and to suggest emerging directions for future research. The writing is character research, with a descriptive qualitative setting. The results of the research show that Valentino Rossi's life journey in achieving various achievements cannot be separated from a strong life mindset by compromising between the realities of life and spiritual practice. This fact in the domain of Islamic education is a form of integrating knowledge organically, comprehensively and holistically. This can be used as an impression for Islamic education. Research implications: the need for improvised research to narrow the dichotomy of science and life reality. The study suggests multidisciplinary research as a starting point for the development of Islamic education.